Location-Dependent Human Osteoarthritis Cartilage Response to Realistic Cyclic Loading: Ex-Vivo Analysis on Different Knee Compartments - Assirelli, Elisa; Caravaggi, Paolo; Mazzotti, Antonio; Ursini, Francesco; Leardini, Alberto; Belvedere, Claudio; Neri, Simona (Frontiers in Bioengineering and Biotechnology, 2022)
Objective - Osteoarthritis (OA) is a multifactorial musculoskeletal disorder affecting mostly weight-bearing joints. Chondrocyte response to load is modulated by inflammatory mediators and factors involved in extracellular cartilage matrix (ECM) maintenance, but regulatory mechanisms are not fully clarified yet. By using a recently proposed experimental model combining biomechanical data with cartilage molecular information, basally and following ex-vivo load application, we aimed at improving the understanding of human cartilage response to cyclic mechanical compressive stimuli by including cartilage original anatomical position and OA degree as independent factors. Methods - 19 mono-compartmental Knee OA patients undergoing total knee replacement were recruited. Cartilage explants from four different femoral condyles zones and with different degeneration levels were collected. The response of cartilage samples, pooled according to OA score and anatomical position was tested ex-vivo in a bioreactor. Mechanical stimulation was obtained via a 3-MPa 1-Hz sinusoidal compressive load for 45-min to replicate average knee loading during normal walking. Samples were analysed for chondrocyte gene expression and ECM factor release. Results – Non parametric univariate and multivariate (generalized linear mixed model) analysis was performed to evaluate the effect of compression and IL-1β stimulation in relationship to the anatomical position, local disease severity and clinical parameters with a level of significance set at 0.05. We observed an anti-inflammatory effect of compression inducing a significant downmodulation of IL-6 and IL-8 levels correlated to the anatomical regions, but not to OA score. Moreover, ADAMTS5, PIICP, COMP and CS were upregulated by compression, whereas COL-2CAV was downmodulated, all in relationship to the anatomical position and to the OA degree. Conclusions - While unconfined compression testing may not be fully representative of the in-vivo biomechanical situation, this study demonstrates the importance to consider the original cartilage anatomical position for a reliable biomolecular analysis of knee OA metabolism following mechanical stimulation.